Capacity building for new economic actors in Granma: a systematized experience (Original) (REDEL. Revista Granmense de Desarrollo Local, 2025)
The project "MSMEs and enterprises contributing to sustainable, effective and inclusive territorial development in Cuba" is coordinated by the United Nations Development Program and the Ministry of Economy and Planning, with the support of the Swedish International Development Cooperation Agency in coordination with the provincial government and the Center for the Study of Management and Local Development of the University of Granma. As part of this project, free training courses were given in different spaces, which were aimed at owners of private MSMEs, cooperatives, self-employment projects and local development projects, which are developed in prioritized sectors of the economy. The objective of the article is to analyze the results obtained in the capacity building of new economic actors from the aforementioned project during 2023. The research had a participatory approach, of collective construction of learning and new knowledge, based on the experience developed by the actors themselves. Among its challenges, the project proposes to develop a system of capacity building for MSMEs and entrepreneurship that promotes initiatives and contributes to the promotion of competitive businesses, with a gender focus and that enhance the empowerment of women and young people in the localities of Granma.
Keywords: new economic actors; capacity building; entrepreneurs; MSMEs